Rapid and efficient analysis of gene function using CRISPR‐Cas9 in Xenopus tropicalis founders. (24th May 2016) - Shigeta, Mitsuki; Sakane, Yuto; Iida, Midori; Suzuki, Miyuki; Kashiwagi, Keiko; Kashiwagi, Akihiko; Fujii, Satoshi; Yamamoto, Takashi; Suzuki, Ken‐ichi T.
Abstract : Recent advances in genome editing using programmable nucleases, such as zinc finger nucleases (ZFNs), transcription activator‐like effector nucleases (TALENs) and the clustered regularly interspaced short palindromic repeats (CRISPR)‐Cas system, have facilitated reverse genetics in Xenopus tropicalis . To establish a practical workflow for analyzing genes of interest using CRISPR‐Cas9, we examined various experimental procedures and conditions. We first compared the efficiency of gene disruption between Cas9 protein and mRNA injection by analyzing genotype and phenotype frequency, and toxicity. Injection of X. tropicalis embryos with Cas9 mRNA resulted in high gene‐disrupting efficiency comparable with that produced by Cas9 protein injection. To exactly evaluate the somatic mutation rates of on‐target sites, amplicon sequencing and restriction fragment length polymorphism analysis using a restriction enzyme or recombinant Cas9 were performed. Mutation rates of two target genes ( slc45a2 and ltk ) required for pigmentation were estimated to be over 90% by both methods in animals exhibiting severe phenotypes, suggesting that targeted somatic mutations were biallelically introduced in almost all somatic cells of founder animals. Using a heteroduplex mobility assay, we also showed that off‐target mutations were induced at a low rate. Based on our results, we propose a CRISPR‐Cas9‐mediated gene disruption workflow for a rapid and efficient analysis of gene function using X. tropicalis founders. Abstract : Targeted gene disruption of tyrosinase (tyr), solute carrier family 45 member 2 (slc45a2) and leukocyte tyrosine kinase (ltk) using Cas9 protein or Cas9 mRNA with sgRNA in X. tropicalis founders.